Epizootic rabbit enteropathy - Current data and control - XYLOURI (Ε. ΞΥΛΟΥΡΗ), E.; FRAGKIADAKIS (Μ. ΦΡΑΓΚΙΑΔΑΚΗΣ), M. (Journal of the Hellenic Veterinary Medical Society, 2017)
Epizootic Rabbit Enteropathy (ERE) is an important syndrome that occurred in European rabbit farms the last ten years and is linked to massive deaths, mainly during the fattening period. ERE was first observed in France, in 1997, and was quickly spread in all rabbit-breeding European countries, e.g. Italy, Spain, Portugal, Belgium, Netherlands, Hungary, Germany, Great Britain and Greece. In Greece, ERE has been clinically identified since 2003 in several commercial rabbit farms, causing severe economic loss in country's rabbit farming sector. In other continents no ERE cases have been reported up to today. ERE is characterized by very high mortality, reaching up to 30-80%. The exact etiology of the syndrome is still unclarified, although in several cases, various known pathogens have been isolated, e.g. coccidia, E. coli, Clostridium spp., Enteroviruses, Rota, virus. Treatment is only symptomatic and is mainly based on the use of antibiotics. Prescribed antibiotics against ERE are thiamouline and tylozine. But, the antibiotic of choice is the water soluble bacitracin, which is exclusively permitted only for use in rabbit farms.